ANALYSIS OF QUALITY IMPROVEMENT USING STATISTICAL PRPOCESS CONTROL TOOLS TO REDUCE THE DEFECT LEVEL OF GREY FABRIC PRODUCT (A CASE STUDY AT PT SARI WARNA ASLI II BOYOLALI) - Yuni Pambreni; Karnowahadi Karnowahadi; Budi Prasetya (JOBS (Jurnal Of Business Studies), 2016)
This study aims to find out the implementation of quality control of products at PT Sari WarnaAsli II Boyolali by using statistical methods, to identify the type of dominant product defects and to identify the factors that resulted in product defect including Light Filling Bar, Miss Pick, and Filling Bar. The method of collecting data are interview, observation, and literature review. Analysis of quality control is done by using Statistical Process Control tools such as check sheet, histogram, c chart, pareto chart, and fishbone chart. Check sheet and histogram are used to present data become easier to be understood for further analysis. C chart analysis result indicate that there are 27 days in March 2016 in which the data is out of control limits, it means that quality control in the company needs further improvement. According to pareto analysis, the dominant of defects are Light Filling Bar (45,3%), Miss Pick (28,8%), and Filling Bar (25,9%). From fishbone chart, it can be known that the main causes that trigger the defects are derived from method factor, personnel (man) factor, and machine factor. The company could take preventive and corrective measures to reduce the defect level and improve quality among others, by enhancing supervision, improving work assessment, and regenerating machines.